Consumer Engagement In International Marketing: A Conceptual Review of Cross-Cultural Perspectives - Stefani Angmalisang; Vanesa Mongan; Nur Lahati; Febryanti Ragho; Ariane Worotitjan; Anugrah Oping; Yuliani Kadua; Cindi Mamahit; Christi David; Mesya Sumarandak (Penerbit Jurnal Indonesia, 2026)
Globalization has significantly influenced how brands establish and sustain relationships with consumers in various cultural contexts. This study aims to explore consumer engagement as a strategic dimension in international marketing by analyzing emotional, cognitive, and behavioral involvement as key determinants of brand loyalty and trust. Using a conceptual and theoretical synthesis approach, this paper reviews relevant literature in global consumer behavior, digital branding, and cross-cultural adaptation to understand how engagement practices contribute to brand authenticity and cultural resonance. Findings from the analysis highlight that global brands such as Starbucks, Nike, and Skintific have effectively employed localized engagement strategies to strengthen consumer relationships across diverse markets. The study concludes that consumer engagement serves as a central factor in achieving sustainable competitiveness within the post-pandemic digital era (2020–2025). These insights contribute to the advancement of international marketing theory and provide practical implications for global marketers adapting to cultural diversity and digital transformation.